Behavior of the equivalent slab thickness over three European stations - Mosert, Marta Estela (2013)
The total electron content (TEC) derived from the global positioning system (GPS) and the F2-layer peak electron density obtained from Digisonde data have been used to study the diurnal, seasonal and solar activity variations of the ionospheric equivalent slab thickness (s) over three European stations located at Pruhonice (50.0N,15.0E), Ebro (40.8N,0.5E) and El Arenosillo (37.1N,353.3E). The diurnal variation of the s is characterized by daytime values lower than nighttime ones for all seasons at low solar activity while daytime values larger than nighttime characterizes the diurnal variation for summer at high solar activity. A double peak is noticeable at dusk and at dawn, better expressed for winter at low solar activity. The seasonal variations of s depend on local time and solar activity, the daytime values of s increases from winter to summer whereas nighttime values of s show the opposite. The effect of the solar activity on s depends on local time and season, there being very sensitive for winter nighttime values of s. The results of this study are compared with those presented by other authors.